Convergent and Divergent Thinking Skills in Electrical Engineering Gaming Framework - Balavendran Joseph, Rani Deepika (European Journal of Applied Sciences, 2021)
This paper focuses on the participants who are categorized based on the number of times they played the same level in an online scientific game. An open-source scientific puzzle game UNTANGLED is used to perform this research. Telemetry data of more than 600 players is extracted from the database is divided into two groups: single (players who played a puzzle only one time) and multiple (players who played the same puzzle more than one time). Analysis performed on these two groups helps to examine convergent and divergent thinking skills. Statistical tests were performed to assist in learning the significance of the two groups based on dependent variables score and type of moves used in the gaming framework. This study is performed by considering more than 700 players’ solutions. The findings obtained show that the single and multiple groups have no significant difference in their performance, and multiple group players obtained top scores alongside single group players. Results show that single group players could have convergent thinking that can provide only one solution for a given problem. In contrast, multiple group players could possess divergent thinking that can offer diverse solutions to the same problem from different perspectives. Finally, this paper dispenses recommendations for STEM educators and scientific game designers to develop open-ended frameworks that reward both thinking competencies. The novelty of this study is to show the consequences of including features that enhance both convergent and divergent thinking skills to solve open-ended problems in electrical engineering.